Current status and novel directions in triple negative breast cancer patients. Risk factors. Role of the platinum-based chemotherapy - Olivia IONESCU; Irina BALESCU; Nicolae BACALBASA (Romanian Journal of Medical Practice, 2016)
Rationale. Breast cancer (BC) has been recognized to be the most common type of cancer in women all over the world. One of the most aggressive subtype of BC is the triple negative breast cancer (TNBC) which is defined by the absence of estrogen receptor (ER) and progesterone receptor (PR) as well as the lack of over expression of the human epidermal growth factor 2 (HER 2). Aim. As the estrogen and progesterone receptors as well as the expression of HER2 are lacking, a targeted therapy with anti-hormone agents and anti-HER2 cannot be utilized, the therapeutic possibilities for TNBC women are limited. The aim of this review is to present the current scientific data as well as the latest research in TNBC with focus on the risk factors as well as the current role of platinum-based chemotherapeutic agents and their future implications in TNBC treatment. Method. Information about the risk factors associated to TNBC as well as the chemotherapeutic regimens was searched through Pubmed and Medline using controlled vocabulary (e.g. breast cancer) and key words (e.g. neoadjuvant, triple negative, platinum). Systematic reviews, randomized and controlled clinical trials were analyzed. No restrictions regarding date or language were used. Conclusions. TNBC is a complex and heterogeneous disease, divided into many subtypes and with an aggressive evolution. Premenopausal women and African American women are far more likely to develop TNBC. More research is required in order to confirm the association between obesity, BMI, parity, use of oral contraceptives, alcohol and cigarette smoking and TNBC. Randomized clinical trials presented at the San Antonio Symposium suggest that platinum chemotherapy play an important role in the treatment of TNBC, especially early stage TNBC. Tumor-based measures of genomic instability will help to clarify the optimal use and activity of platinum in TNBC. However, it is clear than more epidemiological studies as well as the discovery of novel therapeutic possibilities are mandatory in order to unravel the complexity of this BC subtype, hence offering a chance to women diagnosed with TNBC.